Perilaku Cyberbullying Siswa SMK: Kajian Literatur Sistematis - Susanti, Nur Ainy Pricillia; Habsy, Bakhrudin All; Christiana, Elisabeth; Hariastuti, Retno Tri (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2024)
Along with advances in technology in the current era, of course, it cannot be separated from human life, especially at the teenage stage. Various facilities provide a lot of convenience and comfort with just one